Command authority [large type] - Clancy, Tom, 1947-2013; Greaney, Mark (Clancy, Tom, 1947-2013. Jack Ryan novel., 2013)
There's a new strong man in Russia whose rise to power is based on a dark secret hidden decades in the past. The solution to that mystery lies with a most unexpected source: President Jack Ryan.